Digital Marketing Strategy in Digital Business to Enhance MSME Competitiveness - Hanny Safitri; Sipah Audiah; David Edmond (Pandawan Sejahtera Indonesia, 2026)
The rapid expansion of digital business presents significant opportunities for Micro, Small, and Medium Enterprises (MSMEs) to enhance their competitiveness. However, many MSMEs still face challenges in effectively implementing digital marketing strategies due to limited capabilities and strategic orientation. This study aims to analyze the role of digital marketing strategies in improving MSME competitiveness within the digital business environment, with a particular focus on the mediating role of digital capabilities. A quantitative approach was employed using survey data collected from MSME actors engaged in digital business activities. The data were analyzed using Structural Equation Modeling (SEM) to examine the relationships between digital marketing strategies, digital capabilities, and competitiveness. The findings reveal that digital marketing strategies have a significant positive effect on MSME competitiveness. Additionally, digital capabilities play a crucial mediating role, strengthening the impact of marketing strategies on competitive performance. The results highlight the importance of adopting integrated, data-driven, and customer-oriented digital marketing practices to achieve sustainable competitiveness. This study contributes to the growing literature on digital business and MSME development by providing empirical evidence on the interplay between strategy and capability. Managerially, the findings suggest that MSMEs should invest in developing digital skills and strategic marketing approaches to remain competitive in an increasingly dynamic digital landscape.